Some Best Proximity Point Results for \(\mathcal{MT}\)-Rational Cyclic Contractions in \(S\)-Metric Space - Chaipornjareansri, Somkiat (Communications in Mathematics and Applications, 2020)
In this paper, we use the concept of \(\mathcal{MT}\)-function to establish the best proximity point results for a certain class of proximal cyclic contractive mappings in \(S\)-metric spaces. Our results extend and improve some known results in the literature. We give an example to analyze and support our main results.
Keywords: cyclic mapping; best proximity point; \(\mathcal{MT}\)-function (\(\mathcal{R}\)-function); \(S\)-metric space